Synchronization of Legislation in Realizing Disaster Risk Reduction: Sinkronisasi Peraturan Perundang-Undangan dalam Mewujudkan Pengurangan Risiko Bencana - Shandra Lisya Wandasari (Universitas Negeri Semarang, 2012)
Disaster risk reduction is a program undertaken by the stakeholders to strive for sustainability, participation of all parties. This study aims to analyze the importance of synchronization of legislation in the field of disaster risk reduction. The results showed that the synchronization of legislation important, wheather in the disaster management, both sociologically, which includes economic, social , and cultural as well as empirically that showed resilience and the condition of the study area based on the level of disaster risk, threat, vulnerability and capacity; and urgency normatively between central and local level regulation. The synchronization of the model legislation in proper disaster management sector is a model of vertical synchronization based on systematic synchronization and synchronization also synchronizes the law relating to the principles of the legislation.